Three new species of the genus Sulcolotis Miyatake (Coleoptera, Coccinellidae, Sticholotidini) from the Philippines - Liu, Liyuan; Wang, Yan; Guo, Qiuhong; Chen, Xiaosheng; Wang, Xingmin (Zootaxa, 2022)
The genus Sulcolotis Miyatake, 1994 is reviewed. Three new species (S. threadis sp. n., S. ovalis sp. n., and S. xanthomarginalis sp. n.) from the Philippines are described and illustrated in the present paper. A key to species of the genus Sulcolotis is also provided.